(untitled) (Palimpsesto, 2017)
Territories and regions are constantly constructed in a historical process that includes the representational. The analysis of films shot in Patagonia is of great importance since it deepens our knowledge of the region and of the way its identity is constantly re-shaping. The present paper analyses the representations about the Patagonia constructed by Historias Mínimas (Carlos Sorín, 2002). This film reclaims the little everyday stories showing images and subjects rejected by the entertainment industry. We conclude that, although the film discourse cannot be thought of as counter-hegemonic, it does presents critical features in that the Patagonia appears as a place in conflict where the ravages of neoliberalism are gone through and resisted.